Freedom's champion--Elijah Lovejoy - Simon, Paul, 1928-2003 (Southern Illinois University Press, 1994)
"In this revised edition of his earlier biography, Paul Simon provides an inspiring account of the life and work of Elijah Lovejoy, an avid abolitionist in the 1830s and the first martyr to freedom of the press in the United States."--Jacket